All-solid secondary battery
The full-solid secondary battery design with specific Ni, Co, and Mn molar ratios in the positive electrode layer and a solid electrolyte separator addresses discharge capacity and charging efficiency issues by minimizing volume changes, resulting in improved performance.
Patent Information
- Application Number
- JP2022570832
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-12-22
- Publication Date
- 2025-01-29
- Estimated Expiration
- 2040-12-22
AI Technical Summary
Existing all-solid lithium-ion secondary batteries face issues with reduced discharge capacity and charging efficiency due to the use of lithium composite oxides with conventional molar ratios, which lead to volume changes during charging and discharging, causing peeling and suppressed lithium ion diffusion.
A full-solid secondary battery design utilizing a positive electrode layer composed of lithium composite oxides with specific molar ratios of Ni, Co, and Mn (0.19 ≤ Ni/(Ni+Co+Mn) ≤ 0.41, 0.49 ≤ Co/(Ni+Co+Mn) ≤ 0.71, and 0.09 ≤ Mn/(Ni+Co+Mn) ≤ 0.11, along with a solid electrolyte separator layer and a negative electrode layer, to minimize volume changes and enhance discharge capacity.
The proposed battery configuration significantly improves discharge capacity and charging efficiency by reducing volume changes and peeling, thereby enhancing the overall performance of the battery.
Smart Images

Figure 0007624017000001 
Figure 0007624017000002
Abstract
Description
[Technical field]
[0001] The present invention relates to an all-solid-state secondary battery, and in particular to an all-solid-state lithium ion secondary battery. [Background technology]
[0002] As a positive electrode active material layer for a lithium ion secondary battery, a powder dispersion type positive electrode obtained by kneading and molding a powder of a lithium composite oxide (typically a lithium transition metal oxide) with additives such as a binder and a conductive agent is widely known. Such a powder dispersion type positive electrode contains a relatively large amount (for example, about 10% by weight) of a binder that does not contribute to the capacity, so the packing density of the lithium composite oxide as the positive electrode active material is low. For this reason, the powder dispersion type positive electrode has a large room for improvement in terms of capacity and charge / discharge efficiency. Therefore, attempts have been made to improve the capacity and charge / discharge efficiency by forming the positive electrode or the positive electrode active material layer from a lithium composite oxide sintered plate. In this case, since the positive electrode or the positive electrode active material layer does not contain a binder, it is expected that a high capacity and good charge / discharge efficiency can be obtained by increasing the packing density of the lithium composite oxide.
[0003] In addition, in lithium ion secondary batteries, a liquid electrolyte (electrolytic solution) using a flammable organic solvent as a diluting solvent has been conventionally used as a medium for transferring ions. In batteries using such an electrolyte, problems such as leakage of the electrolyte, fire, explosion, etc. may occur. In order to solve such problems, and to ensure essential safety, development of all-solid-state batteries is being promoted in which a solid electrolyte is used instead of a liquid electrolyte and all other elements are composed of solids. Since such all-solid-state batteries use a solid electrolyte, there is no risk of fire, they do not leak, and they are less likely to cause problems such as deterioration of battery performance due to corrosion.
[0004] Various all-solid-state batteries using a sintered body electrode and a solid electrolyte have been proposed. For example, in Patent Document 1 (WO2019 / 093222A1), an oriented positive electrode plate that is a lithium composite oxide sintered plate with a porosity of 10 to 50%, contains Ti, and has a melting point lower than that of the oriented positive electrode plate or the negative electrode plate, and a solid electrolyte having a melting point lower than the decomposition temperature. An all-solid-state lithium battery including a negative electrode plate capable of inserting and extracting lithium ions at 0.4 V (vs. Li / Li + ) or higher is disclosed. In this document, various materials such as Li3OCl and xLiOH·yLi2SO4 (where x + y = 1 and 0.6 ≦ x ≦ 0.95) (for example, 3LiOH·Li2SO4) are disclosed as such solid electrolytes having a low melting point. Such a solid electrolyte can penetrate into the voids of the electrode plate as a melt, and strong interfacial contact can be realized. As a result, it is said that a significant improvement in battery resistance and rate performance during charge and discharge, as well as a significant improvement in battery manufacturing yield, can be achieved. Further, in Patent Document 2 (WO2015 / 151566A1), Li p (Ni x ,Co y ,Mn z )O2 (where 0.9 ≦ p ≦ 1.3, 0 < x < 0.8, 0 < y < 1, 0 ≦ z ≦ 0.7, and x + y + z = 1) is an oriented positive electrode plate having a layered rock salt structure of a basic composition, and a solid electrolyte layer composed of a Li-La-Zr-O-based ceramic material and / or a lithium phosphorous oxynitride (LiPON)-based ceramic material, and a negative electrode layer. An all-solid-state lithium battery is disclosed. The positive electrode compositions actually evaluated in this Patent Document 2 have a molar ratio of Ni:Co:Mn of 5:2:3 or 1:1:1.
Prior Art Documents
Patent Documents
[0005]
Patent Document 1
Patent Document 2
Summary of the Invention
[0006] The present inventors have found that, among the above-mentioned low-melting-point solid electrolytes, LiOH·Li2SO4-based solid electrolytes, such as 3LiOH·Li2SO4, exhibit high lithium ion conductivity. However, when a cell was constructed using a conventionally used lithium composite oxide sintered plate with a Ni:Co:Mn molar ratio of 5:2:3 as the positive electrode together with a LiOH·Li2SO4-based solid electrolyte, such as 3LiOH·Li2SO4, and the cell was operated, it was found that the discharge capacity was lower than the theoretical capacity expected from the amount of active material.
[0007] The present inventors have now discovered that by constructing an all-solid-state secondary battery using a porous sintered plate of a lithium composite oxide containing Ni, Co and Mn in a molar ratio within a predetermined range as a positive electrode layer, it is possible to significantly improve charge-discharge characteristics such as discharge capacity.
[0008] Therefore, an object of the present invention is to provide an all-solid-state secondary battery with significantly improved charge-discharge characteristics such as discharge capacity.
[0009] According to one aspect of the present invention, Ni, Co and Mn are 0.19≦Ni / (Ni+Co+Mn)≦0.41, 0.49≦Co / (Ni+Co+Mn)≦0.71, and 0.09≦Mn / (Ni+Co+Mn)≦0.11 A positive electrode layer including a porous sintered plate composed of a lithium composite oxide having a layered rock salt structure containing the lithium composite oxide in a molar ratio satisfying the following: a negative electrode layer including a porous sintered plate made of a negative electrode active material; a solid electrolyte interposed between the positive electrode layer and the negative electrode layer as a separator layer and also filled in the pores of the porous sintered plate of the positive electrode layer and the negative electrode layer; An all-solid-state secondary battery comprising: DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] All-solid-state secondary battery The all-solid-state secondary battery of the present invention includes a positive electrode layer, a negative electrode layer, and a solid electrolyte. The positive electrode layer includes a porous sintered plate made of a lithium composite oxide having a layered rock salt structure. The negative electrode layer includes a porous sintered plate made of a negative electrode active material. The solid electrolyte is interposed between the positive electrode layer and the negative electrode layer as a separator layer, and is also filled in the holes of the porous sintered plates of the positive electrode layer and the negative electrode layer. The lithium composite oxide contains Ni, Co, and Mn in molar ratios that satisfy 0.19≦Ni / (Ni+Co+Mn)≦0.41, 0.49≦Co / (Ni+Co+Mn)≦0.71, and 0.09≦Mn / (Ni+Co+Mn)≦0.11. In this way, by using a porous sintered plate of a lithium composite oxide containing Ni, Co, and Mn in a molar ratio within a predetermined range as the positive electrode layer to configure an all-solid-state secondary battery, it is possible to significantly improve charge and discharge characteristics such as discharge capacity.
[0011] As mentioned above, all-solid-state lithium batteries impregnated with a low-melting point solid electrolyte such as a LiOH·Li2SO4-based solid electrolyte are known (see, for example, Patent Document 1), and the solid electrolyte penetrates the gaps of the electrode plate as a melt, thereby realizing interface contact. As a result, it is possible to improve the battery resistance and rate performance during charging and discharging, as well as the yield of battery production. However, when a lithium composite oxide sintered plate having a molar ratio of Ni:Co:Mn of 5:2:3 as conventionally used is used as the positive electrode, and a cell is constructed together with a LiOH·Li2SO4-based solid electrolyte such as 3LiOH·Li2SO4, and the battery is operated, it was found that the discharge capacity is lower than the theoretical capacity expected from the amount of active material. This problem is conveniently solved by using a porous sintered plate of a lithium composite oxide containing Ni, Co, and Mn in a molar ratio within the above range as the positive electrode layer. This is thought to be because the expansion and contraction or volume change accompanying charging and discharging of the lithium composite oxide containing Ni, Co, and Mn in a molar ratio within the above range is small. In fact, when the all-solid-state battery after charging and discharging with deteriorated performance was analyzed, gaps were found between the solid electrolyte impregnated in the positive electrode sintered plate of Ni:Co:Mn=5:2:3 and the positive electrode active material particles constituting the positive electrode sintered plate. In other words, since the lithium composite oxide particles of Ni:Co:Mn=5:2:3 that have been used conventionally have the property of shrinking during charging, it is considered that the stress caused by particle shrinkage caused peeling between the positive electrode plate and the solid electrolyte, suppressing the diffusion of Li ions, and thus reducing the discharge capacity of the all-solid-state battery. In this regard, the porous sintered plate made of the lithium composite oxide in the above composition range of the present invention has small expansion and contraction or volume change during charging and discharging, so that the above-mentioned problems are unlikely to occur, and as a result, it is considered that the charge and discharge characteristics such as discharge capacity are significantly improved.
[0012] (1) Positive electrode layer The positive electrode layer includes a porous sintered plate composed of a lithium composite oxide having a layered rock salt structure as a positive electrode active material. In other words, the porous sintered plate has a structure in which a plurality of primary particles composed of a lithium composite oxide having a layered rock salt structure are bonded together. This lithium composite oxide contains Ni, Co, and Mn in a molar ratio that satisfies 0.19≦Ni / (Ni+Co+Mn)≦0.41, 0.49≦Co / (Ni+Co+Mn)≦0.71, and 0.09≦Mn / (Ni+Co+Mn)≦0.11, more preferably in a molar ratio that satisfies 0.29≦Ni / (Ni+Co+Mn)≦0.31, 0.59≦Co / (Ni+Co+Mn)≦0.61, and 0.09≦Mn / (Ni+Co+Mn)≦0.11. As described above, a composition (molar ratio) within the above range brings about a significant improvement in charge / discharge characteristics such as discharge capacity. In this regard, the behavior of the volume change during charging and discharging of lithium composite oxides containing Ni, Co, and Mn (hereinafter abbreviated as NCM) varies depending on the composition, particularly the molar ratio of Ni, Co, and Mn. However, if the composition (molar ratio) is within the above range, the expansion and contraction or volume change of the NCM porous sintered plate accompanying charging and discharging is small, and some compositions have almost no volume change during charging and discharging (for example, Ni:Co:Mn=3:6:1). Therefore, it is considered that the peeling between the NCM porous sintered plate and the solid electrolyte is suppressed, and a significant improvement in the charge and discharge characteristics such as discharge capacity is realized. Specific examples of NCM compositions (molar ratios) within the above range include Ni:Co:Mn=2:7:1, 3:6:1, and 4:5:1, and Ni:Co:Mn=3:6:1 is particularly preferable. In this way, when the molar ratio of Co is increased, the volume change of the NCM porous sintered plate during charging and discharging is less likely to occur. On the other hand, in the case of lithium composite oxides with a small molar ratio of Co, such as Ni:Co:Mn=5:2:3 or 8:1:1, the volume of the NCM porous sintered plate changes significantly during charging and discharging.
[0013] The NCM porous sintered plate was measured by X-ray diffraction (XRD), and the diffraction intensity I
[0104] Diffraction intensity due to (003) plane for I
[0003] The degree of orientation I is defined as the ratio of
[0003] / I
[0104] is 1.2 to 3.6, preferably 1.2 to 3.5, more preferably 1.2 to 3.0, and even more preferably 1.2 to 2.6. Within such a range, the volume change of the NCM porous sintered plate during charging and discharging is more unlikely to occur, peeling between the sintered plate and the solid electrolyte is suppressed, and the charge and discharge characteristics such as the discharge capacity can be more effectively improved. Here, in a lithium composite oxide having a layered rock salt type crystal structure such as NCM, there are crystal faces (faces other than the (003) face, for example, the (101) face and the (104) face) in which lithium ions enter and exit well, and a (003) face in which they do not. In this specification, the diffraction intensities by XRD of the (003) face and the (104) face are conveniently used as indexes for calculating the degree of orientation.
[0014] Orientation degree I within the above range
[0003] / I
[0104] The reason why charge / discharge characteristics such as discharge capacity improve when the NCM is in the form of a powder (i.e., a form that is not a sintered body) can be considered as follows. First, as a premise, we will explain the concept of orientation / non-orientation. When the NCM is in the form of a powder (i.e., a form that is not a sintered body), the particle arrangement is random, so there is no bias in the orientation of the crystal planes. This is called non-orientation. On the other hand, in a form such as a sintered plate, the particle arrangement is fixed, so bias in the orientation of the crystal planes is likely to occur, and this state is called orientation. In this regard, the NCM porous sintered plate has an orientation degree I within the above-mentioned range,
[0003] / I
[0104] Then, the degree of orientation of the NCM powder, I
[0003] / I
[0104] Since the value is equal to or close to the values of 1.4 (for example, 1.4 (composition of Ni:Co:Mn=5:2:3) or 2.3 (composition of Ni:Co:Mn=3:6:1)), it can be said that it is close to non-orientation (random), that is, it is essentially not oriented (or not very oriented). NCM primary particles have anisotropy in their expansion and contraction behavior during charging and discharging (this tendency is particularly prominent in NCM with Ni:Co:Mn=3:6:1). However, if the NCM porous sintered plate is close to non-orientation (random), the anisotropy of the expansion and contraction of the NCM primary particles that compose it is offset or mitigated by the randomness of the crystal orientation, so that the expansion and contraction of the entire NCM porous sintered plate is small. As a result, the volume change of the NCM porous sintered plate during charging and discharging is even less likely to occur, and peeling between the sintered plate and the solid electrolyte is suppressed, which is considered to more effectively improve the charge and discharge characteristics such as the discharge capacity.
[0015] The porosity of the NCM porous sintered plate is 10 to 40%, preferably 15 to 38%, more preferably 18 to 36%, and even more preferably 20 to 33%. When the porosity is within such a range, the pores can be sufficiently filled with the solid electrolyte, and the ratio of the positive electrode active material in the positive electrode increases, so that the battery can achieve a high energy density. In this specification, the "porosity" refers to the volume ratio of the pores in the sintered plate. This porosity can be measured by image analysis of a cross-sectional SEM image of the sintered plate. For example, the sintered plate is filled with resin, the cross-section is polished by ion milling, and then the polished cross-section is observed with an SEM (scanning electron microscope) to obtain a cross-sectional SEM image (for example, 500 to 1000 times magnification), and the obtained SEM image is analyzed to calculate the ratio (%) of the area of the resin-filled portion to the total area of the electrode active material portion and the resin-filled portion (the portion that was originally a pore), and the porosity (%) of the sintered plate can be calculated. If the measurement can be performed with the desired accuracy, the porosity may be measured without filling the sintered plate with resin. For example, the porosity of a sintered plate (a positive electrode plate removed from an all-solid-state secondary battery) whose pores are filled with a solid electrolyte can be measured while the pores are still filled with the solid electrolyte.
[0016] The average primary particle diameter of the NCM porous sintered plate is preferably 0.4 to 5.0 μm, more preferably 0.5 to 4.0 μm, even more preferably 0.6 to 3.0 μm, particularly preferably 0.8 to 2.5 μm, and most preferably 1.0 to 2.2 μm. Within such a range, improvement of charge / discharge characteristics such as discharge capacity can be more effectively realized. This is thought to be because the anisotropy of expansion and contraction of the lithium composite oxide primary particles accompanying charge / discharge is reduced due to the primary particles being small as described above. In this specification, the "average primary particle diameter" refers to the average diameter of the primary particles contained in the sintered plate of the electrode. This average primary particle diameter can be measured by image analysis of a cross-sectional SEM image of the sintered plate. Specifically, the cross-sectional SEM image (for example, 5000 times magnification) obtained in the same manner as in the above-mentioned porosity measurement can be analyzed, and the average primary particle diameter can be calculated by the intercept method as follows. First, a straight line (segment) with a total length of L is drawn randomly in an SEM image at a magnification of 5000 times, and the number of intersections between the segment and the grain boundaries of the primary particles is determined as n L Calculate D1 = 1.5 × L / n L The average primary particle diameter D1 is calculated by the formula. The above-mentioned operation is carried out twice, changing the position each time, to calculate the average primary particle diameters D2 and D3. The average value of the obtained average primary particle diameters D1, D2, and D3 is calculated, and this is set as the average primary particle diameter D of the porous sintered plate. If the measurement can be performed with the desired accuracy, the average primary particle diameter may be measured without filling the sintered plate with resin. For example, the average primary particle diameter of a sintered plate (a positive electrode plate removed from an all-solid-state secondary battery) whose pores are filled with a solid electrolyte can be measured while the solid electrolyte is still filled.
[0017] The average pore diameter of the NCM porous sintered plate is preferably 0.5 μm or more, more preferably 0.5 to 15.0 μm, even more preferably 0.7 to 15.0 μm, particularly preferably 0.8 to 10.0 μm, and most preferably 0.9 to 8.0 μm. Within such a range, the solid electrolyte portion (solid electrolyte portion at a distance from the interface) that is less susceptible to deterioration due to side reactions between the solid electrolyte and the sintered plate increases. Therefore, it is considered that the element diffusion between the solid electrolyte and the sintered plate is suppressed, and the peeling between the sintered plate and the solid electrolyte due to the deterioration of the solid electrolyte is suppressed. In this specification, the "average pore diameter" is the average value of the diameters of the pores contained in the sintered plate of the electrode. The "diameter" is typically the length of a line segment that divides the projected area of the pores in half (Martin diameter). In the present invention, the "average value" is suitably calculated based on the number of pores. This average pore diameter can be measured by image analysis of a cross-sectional SEM image of the sintered plate. For example, the SEM image obtained in the above-mentioned porosity measurement is analyzed to separate the electrode active material portion and the resin-filled portion (the portion that was originally pores) in the sintered plate, and the maximum Martin diameter of each region in the resin-filled portion is obtained, and the average value of these is taken as the average pore diameter of the sintered plate. If the measurement can be performed with the desired accuracy, the average pore diameter may be measured without filling the sintered plate with resin. For example, the average pore diameter of a sintered plate (a positive electrode plate removed from an all-solid-state secondary battery) whose pores are filled with a solid electrolyte can be measured while the solid electrolyte is still filled.
[0018] From the viewpoint of improving the energy density of the battery, the thickness of the NCM porous sintered plate is preferably 30 to 200 μm, more preferably 50 to 200 μm, and further preferably 80 to 200 μm.
[0019] The NCM porous sintered plate may be produced by any method, and may be produced appropriately by referring to a known method for producing a porous sintered lithium composite oxide. For example, an NCM green sheet may be produced using an NCM raw material powder containing Ni, Co, and Mn in a molar ratio that satisfies 0.19≦Ni / (Ni+Co+Mn)≦0.41, 0.49≦Co / (Ni+Co+Mn)≦0.71, and 0.09≦Mn / (Ni+Co+Mn)≦0.11, and the NCM green sheet may be fired to produce the plate. The properties of the NCM porous sintered plate, such as the porosity, average primary particle size, and average pore size, may be appropriately controlled by controlling the particle size of the NCM raw material powder, using a mixed powder of two or more NCM raw material powders having different particle size distributions, or adjusting the firing conditions.
[0020] (2) Negative electrode layer The negative electrode layer includes a porous sintered plate composed of a negative electrode active material. As the negative electrode active material, a negative electrode active material generally used in lithium secondary batteries can be used. Examples of such general negative electrode active materials include carbon-based materials, metals or semimetals such as Li, In, Al, Sn, Sb, Bi, and Si, or alloys containing any of these. In addition, oxide-based negative electrode active materials may be used.
[0021] Particularly preferred negative electrode active materials are those with a voltage of 0.4V (vs. Li / Li + ) or more and capable of inserting and extracting lithium ions, and preferably contains Ti. A negative electrode active material that satisfies such conditions is preferably an oxide that contains at least Ti, i.e., a titanium-containing oxide. A preferred example of such a negative electrode active material is lithium titanate Li4Ti5O 12 Examples of the lithium-ion-conducting oxide include Li4Ti5O (hereinafter sometimes referred to as LTO), niobium titanium composite oxide Nb2TiO7, and titanium oxide TiO2. More preferred are LTO and Nb2TiO7, and even more preferred is LTO. Although LTO is known to have a typical spinel structure, it can also adopt other structures during charging and discharging. For example, LTO has a structure of Li4Ti5O 12 (spinel structure) and Li7Ti5O 12The reaction proceeds in the coexistence of two phases, i.e., spinel and tetrahydrofuran (rock salt structure). Therefore, LTO is not limited to a spinel structure.
[0022] The porous sintered plate made of the negative electrode active material does not need to contain an electron-conducting agent or binder, so the energy density of the negative electrode can be increased. The pores of the porous sintered plate are filled with a solid electrolyte.
[0023] The porosity of the negative electrode active material or its sintered plate is preferably 20 to 45%, more preferably 20 to 40%, and further preferably 25 to 35%. With a porosity within this range, the pores in the negative electrode active material can be sufficiently filled with the solid electrolyte, and the proportion of the negative electrode active material in the negative electrode increases, so that a high energy density as a battery can be achieved.
[0024] From the viewpoint of improving the energy density of the battery, the thickness of the negative electrode active material or its sintered plate is preferably 40 to 270 μm, more preferably 65 to 270 μm, further preferably 100 to 270 μm, and particularly preferably 107 to 270 μm.
[0025] (3) Solid electrolyte The solid electrolyte is not particularly limited as long as it is applicable to all-solid-state secondary batteries, particularly all-solid-state lithium secondary batteries. For example, garnet-based ceramic materials, nitride-based ceramic materials, perovskite-based ceramic materials, phosphate-based ceramic materials, sulfide-based ceramic materials, borosilicate-based ceramic materials, lithium-halide-based materials, and polymer-based materials can be mentioned. An example of a garnet-based ceramic material is a Li-La-Zr-O-based material (specifically, Li7La3Zr2O 12 etc.), Li-La-Ta-O based materials (specifically, Li7La3Ta2O 12 Examples of nitride ceramic materials include Li3N. Examples of perovskite ceramic materials include Li-La-Zr-O materials (specifically, LiLa 1-x Ti xExamples include O3 (0.04 ≦ x ≦ 0.14), etc. Examples of phosphate-based ceramic materials include lithium phosphate, nitrogen-substituted lithium phosphate (LiPON), Li-Al-Ti-P-O, Li-Al-Ge-P-O, and Li-Al-Ti-Si-P-O (specifically, Li 1+x+y Al x Ti 2-x Si y P 3-y O 12 (0 ≦ x ≦ 0.4, 0 < y ≦ 0.6), etc.). Examples of sulfide-based ceramic materials include LiOH-Li2SO4 and Li3BO3-Li2SO4-Li2CO3. Examples of borosilicate-based ceramic materials include Li2O-B2O3-SiO2. Examples of lithium-halide-based materials include Li3OX (where X is Cl and / or Br), Li2(OH) 1-a F a Cl (where 0 ≦ a ≦ 0.3), and Li2OHX (where X is Cl and / or Br).
[0026] A preferred solid electrolyte is a LiOH·Li2SO4-based solid electrolyte. The LiOH·Li2SO4-based solid electrolyte is a composite compound of LiOH and Li2SO4, and has a typical composition represented by the general formula: xLiOH·yLi2SO4 (wherein x+y=1 and 0.6≦x≦0.95). A representative example is 3LiOH·Li2SO4 (wherein x=0.75 and y=0.25 in the general formula). Preferably, the LiOH·Li2SO4-based solid electrolyte includes a solid electrolyte identified as 3LiOH·Li2SO4 by X-ray diffraction. This preferred solid electrolyte contains 3LiOH·Li2SO4 as the main phase. Whether or not the solid electrolyte contains 3LiOH·Li2SO4 can be confirmed by identifying it using 032-0598 of the ICDD database in the X-ray diffraction pattern. Here, "3LiOH·Li2SO4" refers to a material whose crystal structure can be regarded as the same as that of 3LiOH·Li2SO4, and the crystal composition does not necessarily have to be the same as that of 3LiOH·Li2SO4. In other words, as long as it has the same crystal structure as that of 3LiOH·Li2SO4, the material whose composition is outside of LiOH:Li2SO4=3:1 is also included in "3LiOH·Li2SO4". Therefore, even if the solid electrolyte contains a dopant such as boron (for example, 3LiOH·Li2SO4 in which boron is dissolved and the X-ray diffraction peak is shifted to the high angle side), it is referred to as 3LiOH·Li2SO4 in this specification as long as the crystal structure can be regarded as the same as that of 3LiOH·Li2SO4. Similarly, the solid electrolyte used in the present invention is also allowed to contain inevitable impurities.
[0027] Therefore, the LiOH·Li2SO4-based solid electrolyte may contain a heterogeneous phase in addition to the main phase 3LiOH·Li2SO4. The heterogeneous phase may contain a plurality of elements selected from Li, O, H, S, and B, or may consist of only a plurality of elements selected from Li, O, H, S, and B. Examples of the heterogeneous phase include LiOH, Li2SO4, and / or Li3BO3 derived from the raw materials. These heterogeneous phases are considered to be unreacted raw materials remaining when 3LiOH·Li2SO4 is formed, but since they do not contribute to lithium ion conduction, it is desirable that the amount of them other than Li3BO3 is small. However, the heterogeneous phase containing boron such as Li3BO3 may be contained in a desired amount because it can contribute to improving the lithium ion conductivity retention after long-term storage at high temperatures. However, the solid electrolyte may be composed of a single phase of 3LiOH·Li2SO4 in which boron is dissolved.
[0028] It is preferable that the LiOH·Li2SO4-based solid electrolyte (particularly 3LiOH·Li2SO4) further contains boron. By further containing boron in the solid electrolyte identified as 3LiOH·Li2SO4, it is possible to significantly suppress the decrease in lithium ion conductivity even after long-term storage at high temperatures. It is presumed that boron is incorporated into one of the sites of the crystal structure of 3LiOH·Li2SO4, improving the stability of the crystal structure against temperature. The molar ratio (B / S) of boron B to sulfur S contained in the solid electrolyte is preferably more than 0.002 and less than 1.0, more preferably 0.003 to 0.9, and even more preferably 0.005 to 0.8. If the B / S is within the above range, it is possible to improve the retention rate of lithium ion conductivity. In addition, if the B / S is within the above range, the content of unreacted heterogeneous phases containing boron is low, and therefore the absolute value of lithium ion conductivity can be increased.
[0029] The LiOH·Li2SO4-based solid electrolyte may be a compact of a powder obtained by pulverizing a molten solid, but a molten solid (i.e., solidified after being heated and melted) is preferable.
[0030] The LiOH·Li2SO4-based solid electrolyte is filled into the pores of the porous sintered plates of the positive electrode layer and the negative electrode layer by melting, and the remaining part is interposed as a separator layer (solid electrolyte layer) between the positive electrode layer and the negative electrode layer. The thickness of the separator layer (excluding the part that has entered the pores of the positive electrode layer and the negative electrode layer) is preferably 1 to 500 μm, more preferably 3 to 50 μm, and still more preferably 5 to 40 μm from the viewpoints of charge-discharge rate characteristics and the insulating property of the solid electrolyte.
[0031] (4) Intermediate layer The intermediate layer is preferably provided at the interface between at least one of the positive electrode active material and the negative electrode active material and the solid electrolyte. By providing the intermediate layer, the discharge capacity can be further improved (compared with those without the intermediate layer). Although the detailed mechanism by which the discharge capacity is improved is not clear, it is presumed that the presence of the intermediate layer can suppress the deterioration of the solid electrolyte due to the reaction between the solid electrolyte and the active material. It is more preferable that the intermediate layer exists at the interface between the positive electrode active material and the solid electrolyte, but the intermediate layer may also exist at the interface between the negative electrode active material and the solid electrolyte. The intermediate layer may exist at both the interface between the positive electrode active material and the solid electrolyte and the interface between the negative electrode active material and the solid electrolyte. The thickness of the intermediate layer is not particularly limited as long as the desired discharge capacity improvement effect can be obtained, but is preferably 0.001 to 1 μm, more preferably 0.005 to 0.2 μm, and still more preferably 0.01 to 0.1 μm.
[0032] The intermediate layer is preferably composed of a lithium composite oxide containing at least one selected from the group consisting of Ti, La, Zr, Al, W, Nb, Sn, Ce, Mn, Y, and Ta and Li, and / or an oxide of Y (typically Y2O3). Preferred examples of such lithium composite oxides include oxides of Li and Ti (typically Li2TiO3), oxides of Li, La, and Zr or Li, La, Zr, and Al (typically Li 7-3x Al x La3Zr2O 12 (0 ≦ x < 0.4, more typically 0.02 < x < 0.4)), oxides of Li, La, and Ti (typically Li 0.33 La0.55 TiO3), oxides of Li and W (typically Li2WO4), oxides of Li and Al (typically LiAlO2), oxides of Li and Nb (typically LiNbO3 or LiNb3O8), oxides of Li and Sn (typically LiSnO3), oxides of Li and Ce (typically Li8CeO6), oxides of Li, La and Nb (typically Li5La3Nb2O 12 ), oxides of Li and Mn (typically LiMnO2), oxides of Li and Y (typically LiYO2), oxides of Li and Ta (typically LiTaO3), and any combination thereof, more preferably oxides of Li and Ti (typically Li2TiO3), oxides of Li, La, Zr, and Al (typically Li 6.7 Al 0.1 La3Zr2O 12 ), and oxides of Li, La and Ti (typically Li 0.33 La 0.55 TiO3).
[0033] The intermediate layer can be formed by mixing metal salts such as metal alkoxides or nitrates of one or more metal elements constituting the intermediate layer with alcohol such as ethanol or water in a predetermined molar ratio to prepare a solution, immersing an electrode active material (preferably a sintered plate or particles) in the solution, taking it out, and leaving it in the air to hydrolyze the alkoxide or dry the solvent. In the case of a sintered plate, it is preferable to immerse the plate in the solution under reduced pressure to allow the solution to penetrate into the inside, and it is also preferable to repeat the above-mentioned immersion and leaving it in the air several times (for example, 1 to 20 times). It is preferable to heat treat the electrode active material (preferably a sintered plate or particles) on which the intermediate layer is formed in this way at 400 to 700 ° C for 5 to 60 minutes. In addition, when a metal alkoxide is used, it is preferable to perform the steps from preparation of the solution to immersion in an atmosphere with a dew point of -30 ° C or less so that the solution does not deteriorate due to hydrolysis or the like.
[0034] Manufacturing of all-solid-state secondary batteries The all-solid-state secondary battery can be manufactured, for example, by i) preparing a positive electrode (with an intermediate layer or a current collector formed as necessary) and a negative electrode (with an intermediate layer or a current collector formed as necessary), and ii) sandwiching a solid electrolyte between the positive electrode and the negative electrode and applying pressure, heat, or the like to integrate the positive electrode, the solid electrolyte, and the negative electrode. The positive electrode, the solid electrolyte, and the negative electrode may be bonded by other methods. In this case, examples of the method for forming the solid electrolyte between the positive electrode and the negative electrode include a method of placing a molded body or powder of the solid electrolyte on one electrode, a method of applying a paste of the solid electrolyte powder on the electrode by screen printing, a method of impacting and solidifying the powder of the solid electrolyte by an aerosol deposition method or the like using the electrode as a substrate, and a method of depositing the solid electrolyte powder on the electrode by electrophoresis to form a film. EXAMPLES
[0035] The present invention will be described in more detail with reference to the following examples. 0.3 Co 0.6 Mn 0.1 Lithium composite oxides with a layered rock salt structure containing Li, Ni, Co, and Mn, such as Li4Ti5O2, are abbreviated as "NCM" and Li4Ti5O 12 shall be abbreviated as "LTO."
[0036] First, NCM raw material powders 1 to 6 for producing a positive electrode plate were prepared as follows. Table 1 summarizes the methods for producing these raw material powders.
[0037] [Preparation of NCM raw powder 1] Commercially available (Ni 0.5 Co 0.2 Mn 0.3 )(OH)2 powder (average particle size 9-10 μm) and Li2CO3 powder (average particle size 3 μm) were mixed. The resulting mixed powder was kept at 750°C for 10 hours, and the volumetric D50 particle size was adjusted to approximately 5.5 μm by wet pulverization in a ball mill, and then dried to obtain NCM raw material powder 1.
[0038] [Preparation of NCM raw powder 2] Commercially available (Ni 0.3 Co 0.6 Mn 0.1 )(OH)2 powder (average particle size 7-8 μm) and Li2CO3 powder (average particle size 3 μm) were mixed. The resulting mixed powder was kept at 850°C for 10 hours to obtain NCM raw material powder 2. The volumetric D50 particle size of this powder was approximately 6.5 μm.
[0039] [Preparation of NCM raw material powder 3] NCM raw material powder 2 was adjusted to a volumetric D50 particle size of about 4.3 μm by wet pulverization in a ball mill, and then dried to obtain NCM raw material powder 3.
[0040] [Preparation of NCM raw material powder 4] Commercially available (Ni 0.2 Co 0.7 Mn 0.1 )(OH)2 powder (average particle size 7-8 μm) and Li2CO3 powder (average particle size 3 μm) were mixed. The resulting mixed powder was kept at 850°C for 10 hours, and the volumetric D50 particle size was adjusted to about 4.5 μm by wet grinding in a ball mill, and then dried to obtain NCM raw material powder 4.
[0041] [Preparation of NCM raw material powder 5] Commercially available (Ni 0.4 Co 0.5 Mn 0.1 )(OH)2 powder (average particle size 8-9 μm) and Li2CO3 powder (average particle size 3 μm) were mixed. The resulting mixed powder was held at 850°C for 10 hours, and the volumetric D50 particle size was adjusted to approximately 4.6 μm by wet pulverization in a ball mill, and then dried to obtain NCM raw material powder 5.
[0042] [Preparation of NCM raw material powder 6] Commercially available (Ni 0.3 Co 0.6 Mn 0.1)(OH)2 powder (average particle size 7-8 μm) and Li2CO3 powder (average particle size 3 μm) were mixed. The resulting mixed powder was kept at 750°C for 10 hours, and the volumetric D50 particle size was adjusted to about 0.4 μm by wet pulverization in a ball mill, and then dried to obtain NCM raw material powder 6.
[0043] Using the above raw material powders 1 to 6, positive electrode plates and batteries were produced as described below, and various evaluations were carried out.
[0044] Example 1 (comparison) (1) Preparation of the positive electrode plate (1a) Preparation of NCM green sheet First, NCM raw material powder 1 shown in Table 1 was prepared. This NCM raw material powder 1 was mixed with a solvent, binder, plasticizer, and dispersant for tape casting. After adjusting the viscosity of the resulting paste, it was molded into a sheet on a PET (polyethylene terephthalate) film to produce an NCM green sheet. The thickness of the NCM green sheet was adjusted so that the thickness after firing would be 100 μm.
[0045] (1b) Preparation of NCM sintered plate The NCM green sheet peeled off from the PET film was punched out into a circle with a diameter of 11 mm and placed in a sintering sheath. The temperature was raised to 920°C at a rate of 200°C / h and held for 10 hours for sintering. The thickness of the obtained sintered plate was about 100 μm according to SEM observation. A Au film (thickness 100 nm) was formed as a current collecting layer on one side of this NCM sintered plate by sputtering. In this way, a positive electrode plate was obtained.
[0046] (1c) Deposition of the intermediate layer Tetra-i-propoxytitanium: lithium ethoxide: ethanol were mixed in a molar ratio of 0.0225:0.045:1 to prepare a solution for forming an intermediate layer. The NCM sintered plate prepared in (1b) above was immersed in this solution, the pressure was reduced, and the solution was impregnated into the pores of the positive electrode plate. The above-mentioned operation was carried out in a glove box in an Ar atmosphere with a dew point of -50°C or less. The NCM sintered plate was then taken out of the glove box and left to stand in the air for 10 minutes to form an intermediate layer. The above series of operations was then repeated seven more times (i.e., a total of eight film formations). Finally, the NCM sintered plate was heat-treated at 400°C for 30 minutes to obtain a positive electrode plate with an intermediate layer formed thereon.
[0047] (2) Preparation of negative electrode plate (2a) Preparation of LTO green sheet Commercially available TiO2 powder (average particle size 1μm or less) and Li2CO3 powder (average particle size 3μm) were mixed so that the molar ratio of Li / Ti was 0.84, and then held at 1000℃ for 2 hours to obtain a powder consisting of LTO particles. This powder was adjusted to an average particle size of about 2μm by wet grinding in a ball mill, and then mixed with a solvent, binder, plasticizer, and dispersant for tape casting. After adjusting the viscosity of the obtained paste, this paste was molded into a sheet on a PET film to produce an LTO green sheet. The thickness of the LTO green sheet was adjusted so that the thickness after firing would be 130μm.
[0048] (2b) Preparation of LTO sintered plate The LTO green sheet peeled off from the PET film was punched out into a circle with a diameter of 11 mm and placed in a sintering sheath. The temperature was raised to 850°C at a rate of 200°C / h and held for 2 hours for sintering. The thickness of the resulting sintered plate was approximately 130 μm according to SEM observation. A Au film (thickness 100 nm) was formed as a current collecting layer on one side of this LTO sintered plate by sputtering. In this way, a negative electrode plate was obtained.
[0049] (3) Preparation of solid electrolyte (3a) Preparation of raw material powder mixture Li2SO4 powder (commercial product, purity 99% or more), LiOH powder (commercial product, purity 98% or more), and Li3BO3 (commercial product, purity 99% or more) were mixed in a molar ratio of Li2SO4:LiOH:Li3BO3 = 1:2.6:0.05 to obtain a raw material mixed powder. These powders were handled in a glove box in an Ar atmosphere, and care was taken to prevent deterioration such as moisture absorption.
[0050] (3b) Melt synthesis The raw material powder mixture was placed in a high-purity alumina crucible in an Ar atmosphere. The crucible was then placed in an electric furnace and heat-treated at 430°C for 2 hours in an Ar atmosphere to produce a melt. The melt was then cooled in the electric furnace at 100°C / h to form a solid.
[0051] (3c) Mortar grinding The obtained solidified product was pulverized in a mortar in a glove box in an Ar atmosphere to obtain a solid electrolyte powder having a volume-based D50 particle size of 5 to 50 μm.
[0052] (4) Fabrication of all-solid-state batteries The solid electrolyte powder was placed on the positive plate, and the negative plate was placed on top of that. A weight was then placed on the negative plate, and the plate was heated at 400°C for 45 minutes in an electric furnace. During this process, the solid electrolyte powder melted, and after subsequent solidification, a solid electrolyte layer was formed between the electrode plates. A battery was fabricated using the resulting cell consisting of a positive plate / solid electrolyte / negative plate.
[0053] (5) Evaluation (5a) Degree of orientation XRD (X-ray diffraction) measurement was performed on the positive electrode plate prepared in (1) above. This measurement was performed using an XRD device (Rigaku Corporation, RINT-TTR III) by measuring the XRD profile when X-rays were irradiated onto the plate surface of the positive electrode plate. From this XRD profile, the diffraction intensity (peak height) I due to the (104) plane of NCM was
[0104] Diffraction intensity (peak height) due to the (003) plane for I
[0003] is the ratio of I
[0003] / I
[0104] was calculated and this was taken as the degree of orientation.
[0054] (5b) Thickness and porosity measurements The thickness and porosity (volume%) of the positive electrode plate (NCM sintered plate not containing a solid electrolyte) prepared in (1) above and the negative electrode plate (LTO sintered plate not containing a solid electrolyte) prepared in (2) above were measured as follows. First, the positive electrode plate (or negative electrode plate) was filled with resin, and then the cross section was polished by ion milling, and the polished cross section was observed with an SEM to obtain a cross-sectional SEM image. The thickness was calculated from this SEM image. The SEM images for porosity measurement were images with magnifications of 1000 times and 500 times. The obtained images were binarized using image analysis software (Image-Pro Premier, manufactured by Media Cybernetics), and the ratio (%) of the area of the resin-filled part to the total area of the positive electrode active material (or negative electrode active material) part and the resin-filled part (originally a pore part) in the positive electrode plate (or negative electrode plate) was calculated to obtain the porosity (%) of the positive electrode plate (or negative electrode plate). The threshold value for binarization was set using Otsu's binarization as a discriminant analysis method. The porosity of the positive electrode plate is as shown in Table 2, and the porosity of the negative electrode plate was 38%.
[0055] (5c) Measurement of average pore size The average pore size was measured using the SEM image used in the above porosity measurement as follows. Using image analysis software (Media Cybernetics, Image-Pro Premier), binarization was performed to separate the positive electrode plate (or negative electrode plate) into the positive electrode active material (or negative electrode active material) and the resin-filled portion (the portion that was originally pores). Then, in the region of the resin-filled portion, the maximum Martin diameter of each region was obtained, and the average value thereof was taken as the average pore size (μm) of the positive electrode plate (or negative electrode plate). The average pore size of the positive electrode plate was as shown in Table 2, and the average pore size of the negative electrode plate was 2.1 μm.
[0056] (5d) Average primary particle size Using SEM images (magnification 5000x) obtained in the same manner as in the above porosity measurement, the average primary particle size was calculated by the intercept method as follows. First, a straight line (segment) with a total length L was randomly drawn in the SEM image at a magnification of 5000x, and the number of intersections n between the line segment and the grain boundaries of the primary particles was calculated. L The line length L and the number of intersections between the line and the grain boundaries of the primary particles n L Using the following formula: D1 = 1.5 × L / n L The average primary particle diameter D1 was obtained by the above. The same operation as above was performed twice, changing the position each time, and the average primary particle diameters D2 and D3 were calculated. The average value of the obtained average primary particle diameters D1, D2, and D3 was calculated to be the average primary particle diameter D of the positive electrode plate. The average primary particle diameter D of the positive electrode plate was as shown in Table 2.
[0057] (5e) Measurement of the molar ratio of metal elements in the positive electrode plate The molar ratios of each element, Ni / (Ni+Co+Mn), Co / (Ni+Co+Mn), and Mn / (Ni+Co+Mn), relative to the total content of Ni, Co, and Mn in the positive electrode plate prepared in (1) above, were calculated from the results of metal element analysis by inductively coupled plasma atomic emission spectroscopy (ICP-AES method). The results were within ±0.01 of the molar ratios shown in Table 2.
[0058] (5f) Identification of solid electrolytes by XRD The LiOH·Li2SO4-based solid electrolyte obtained in (3c) above was analyzed by X-ray diffraction (XRD) and identified as 3LiOH·Li2SO4.
[0059] (5g)Charge / discharge evaluation The discharge capacity of the battery prepared in (4) above at an operating temperature of 150° C. was measured in a voltage range of 2.5 V to 1.5 V. This measurement was performed by charging the battery at a constant current and constant voltage until the battery voltage reached the upper limit of the voltage range, and then discharging the battery to the lower limit of the voltage range. At this time, the discharge capacity of Example 1 was regarded as 100, and was used as a standard for showing the discharge capacities of Examples 2 to 9 described later in relative values.
[0060] Example 2 In the preparation of the positive plate in (1) above, a positive plate and a battery were prepared in the same manner as in Example 1, except that NCM raw material powder 3 shown in Table 1 was used instead of NCM raw material powder 1, and various evaluations were performed.
[0061] Example 3 A positive electrode plate and a battery were produced in the same manner as in Example 1, except that in the production of the positive electrode plate in (1) above, NCM raw material powder 4 shown in Table 1 was used instead of NCM raw material powder 1, and various evaluations were performed.
[0062] Example 4 A positive electrode plate and a battery were produced in the same manner as in Example 1, except that in the production of the positive electrode plate in (1) above, NCM raw material powder 5 shown in Table 1 was used instead of NCM raw material powder 1, and various evaluations were performed.
[0063] Example 5 A positive electrode plate and a battery were produced in the same manner as in Example 1, except that in the production of the positive electrode plate in (1) above, NCM raw material powder 6 shown in Table 1 was used instead of NCM raw material powder 1, and various evaluations were performed.
[0064] Example 6 A positive electrode plate and a battery were prepared in the same manner as in Example 1, except that in the preparation of the positive electrode plate in (1) above, 1) NCM mixed powder A containing NCM raw material powders 2 and 6 shown in Table 1 in a mixing ratio (weight ratio) of 90:10 was used instead of NCM raw material powder 1, and 2) the firing temperature was 950°C. Then, various evaluations were performed.
[0065] Example 7 A positive electrode plate and a battery were prepared in the same manner as in Example 1, except that in the preparation of the positive electrode plate in (1) above, 1) NCM mixed powder A containing NCM raw material powders 2 and 6 shown in Table 1 in a mixing ratio (weight ratio) of 90:10 was used instead of NCM raw material powder 1, and 2) the firing temperature was 900°C. Then, various evaluations were performed.
[0066] Example 8 A positive electrode plate and a battery were prepared in the same manner as in Example 1, except that in the preparation of the positive electrode plate in (1) above, 1) NCM mixed powder B containing NCM raw material powders 2 and 6 shown in Table 1 in a mixing ratio (weight ratio) of 70:30 was used instead of NCM raw material powder 1, and 2) the firing temperature was 950°C. Then, various evaluations were performed.
[0067] Example 9 A positive electrode plate and a battery were prepared in the same manner as in Example 1, except that in the preparation of the positive electrode plate in (1) above, 1) NCM mixed powder C containing NCM raw material powders 2 and 6 shown in Table 1 in a mixing ratio (weight ratio) of 95:5 was used instead of NCM raw material powder 1, and 2) the firing temperature was 970°C. Various evaluations were performed on the positive electrode plate and the battery.
[0068] result The specifications of the positive electrode plates and the evaluation results of the cells prepared in each example are shown in Table 2. As mentioned above, the charge / discharge characteristics were compared under the same rate conditions, and the discharge capacity measured in Example 1 (comparison) was regarded as 100, and the relative values were calculated and shown in Table 2.
[0069] [Table 1]
[0070] [Table 2]
Claims
1. Ni, Co and Mn, 0.19≦Ni / (Ni+Co+Mn)≦0.41, 0.49≦Co / (Ni+Co+Mn)≦0.71, and 0.09≦Mn / (Ni+Co+Mn)≦0.11 A positive electrode layer including a porous sintered plate composed of a lithium composite oxide having a layered rock salt structure containing the lithium composite oxide in a molar ratio satisfying the following: a negative electrode layer including a porous sintered plate made of a negative electrode active material; a solid electrolyte interposed between the positive electrode layer and the negative electrode layer as a separator layer and also filled in the pores of the porous sintered plate of the positive electrode layer and the negative electrode layer; An all-solid-state secondary battery equipped with the above.
2. The lithium composite oxide contains Ni, Co and Mn, 0.29≦Ni / (Ni+Co+Mn)≦0.31, 0.59≦Co / (Ni+Co+Mn)≦0.61, and 0.09≦Mn / (Ni+Co+Mn)≦0.11 The all-solid-state secondary battery according to claim 1 , wherein the molar ratio satisfies:
3. The porous sintered plate in the positive electrode layer has a diffraction intensity I due to the (104) plane in an XRD profile measured by X-ray diffraction (XRD). [104] Diffraction intensity I due to the (003) plane [003] The degree of orientation I is defined as the ratio of [003] / I [104] The all-solid-state secondary battery according to claim 1 or 2, wherein the molecular weight is 1.2 to 3.
6.
4. The all-solid-state secondary battery according to any one of claims 1 to 3, wherein the average primary particle diameter of the porous sintered plate in the positive electrode layer is 0.4 to 5.0 μm.
5. The all-solid-state secondary battery according to any one of claims 1 to 4, wherein the average pore diameter of the porous sintered plate in the positive electrode layer is 0.5 to 15 μm.
6. The all-solid-state secondary battery according to any one of claims 1 to 5, wherein the porosity of the porous sintered plate in the positive electrode layer is 10 to 40%.
7. The solid electrolyte is LiOH.Li 2 SO 4 The all-solid-state secondary battery according to any one of claims 1 to 6, wherein the all-solid-state secondary battery is a ZnO-based solid electrolyte.
8. The LiOH.Li 2 SO 4 The solid electrolyte was found to be 3LiOH.Li by X-ray diffraction. 2 SO 4 The all-solid-state secondary battery according to claim 7, comprising a solid electrolyte identified as:
9. The LiOH.Li 2 SO 4 The all-solid-state secondary battery according to claim 7 or 8, wherein the base solid electrolyte further contains boron.
10. The all-solid-state secondary battery according to any one of claims 1 to 9, wherein the negative electrode active material is a titanium-containing oxide.
11. The all-solid-state secondary battery according to claim 10 , wherein the titanium-containing oxide is lithium titanate.
Citation Information
Patent Citations
Ternary positive electrode material with shell-core structure, preparation method thereof and all-solid-state battery
CN111613782A
Nonaqueous electrolyte secondary cell
JP2011076797A
Electrode active material, its production and use
JP2020536367A
All-solid-state lithium cell
WO2015151566A1
All-solid lithium battery and method of manufacturing same
WO2019093222A1